INNOVATIVE APPROACHES TO TRAINING PERSONNEL IN PSYCHOLOGY BASED ON INTERNATIONAL EDUCATIONAL STANDARDS. (Universal International Scientific Journal, 2026)
This scientific thesis analyzes the issue of innovative approaches to training highly qualified personnel in the field of psychology based on international educational standards and experiences. International educational technologies are widely used in the modern education system. Within the framework of the study, priority areas of training qualified specialists based on a competency-based approach, innovative pedagogical methods and practice-oriented curricula were assessed.
Keywords: INNOVATIVE APPROACHES TO TRAINING PERSONNEL IN PSYCHOLOGY BASED ON INTERNATIONAL EDUCATIONAL STANDARDS.